2019
DOI: 10.1038/s41388-018-0664-7
|View full text |Cite
|
Sign up to set email alerts
|

CD44s is a crucial ATG7 downstream regulator for stem-like property, invasion, and lung metastasis of human bladder cancer (BC) cells

Abstract: Over half a million US residents are suffering with bladder cancer (BC), which costs a total $4 billion in treatment annually. Although recent studies report that autophagy-related gene 7 (ATG7) is overexpressed in BCs, the regulatory effects of ATG7 on cancer stem-like phenotypes and invasion have not been explored yet. Current studies demonstrated that the deficiency of ATG7 by its shRNA dramatically reduced sphere formation and invasion in vitro, as well as lung metastasis in vivo in human invasive BC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 70 publications
3
35
0
Order By: Relevance
“…It was reported that the deubiquitylation of CD44s protein by USP28 is required for maintaining the invasive and metastatic phenotypes of CSCs in human bladder cancer [43]. In HCC, c-MYC requires USP28 for its protein stabilization [44], implying that USP28 may also function in liver CSCs. However, NEAT1v1 maintains CSCs properties in a CD44-independent manner, suggesting that NEAT1v1 activates pathways other than USP28.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the deubiquitylation of CD44s protein by USP28 is required for maintaining the invasive and metastatic phenotypes of CSCs in human bladder cancer [43]. In HCC, c-MYC requires USP28 for its protein stabilization [44], implying that USP28 may also function in liver CSCs. However, NEAT1v1 maintains CSCs properties in a CD44-independent manner, suggesting that NEAT1v1 activates pathways other than USP28.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PD-L1 expression levels are correlated with the response to PD-1-PD-L1 blockade in tumor cells [29,30]. Our previous studies have discovered that ATG7 overexpressed plays a critical role in cell invasion, growth and sphere formation of human BC cells [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of ATG7 promotes human BC cells abnormal growth behavior both in vitro and in vivo [19]. Moreover, the TET1/USP28/CD44/RhoGDIβ pathway has been demonstrated to be critical for the oncogenic role of ATG7 [20]. Here, we further discovered another important ATG7 downstream mediator PD-L1, which exerted its oncogenic role in stem-like property, tumorigenesis, and invasion of human BC cells.…”
Section: Introductionmentioning
confidence: 85%
“…Since different CD44 splicing variants may display different functions in breast cancer [12,15,16], we previously examined the expression of CD44 splice variants in breast cancer cell lines, MDA-MB-231 and MDA-MB-435, as well as primary breast cancer, and found that CD44 splicing variants were heterogeneously expressed and CD44s expression was higher in breast cancer cell lines and tissues, which correlated with a higher histology grade [54]. In this study, high level of CD44s mRNA was detected in CD44 + /CD24 − breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD44 + /CD24 − has been widely used as a breast cancer stem cell (BCSC) biomarker [5][6][7][8]. However, whether CD44 is a critically functional molecule in maintaining the characteristics of BCSCs remains controversial [9][10][11][12]. This has limited the development of new therapeutic strategies for breast cancer.…”
Section: Introductionmentioning
confidence: 99%